Macronutrients and their Role in a Healthy Diet for Pregnant Women - qizi, Samadova Nozima Negmat (American Journal of Bioscience and Clinical Integrity, 2025)
The article provides data on the demand of pregnant women living in the Kasbi district of the Kashkadarya region for proteins, fats and carbohydrates. According to the results, the supply of proteins, fats and carbohydrates of respondents 18-29 and 30-39 year olds living in this territory amounted to 77.2 g, 69.4 g, 315.2 g and 79.5 g, 82.1 g, 367.6 g, respectively.